Planning Australia's healthy built environments - Kent, Jennifer 1951-; Thompson, Susan 1954- (Routledge, 2019)
Planning Australia's Healthy Built Environments shines a quintessentially Australian light on the links between land use planning and human health. A burgeoning body of empirical researchdemonstrates the ways urban structure and governance influences human health--and Australia is playing a pivotal role in developing understandings of therelationships between health and the built environment. This book takes a retrospective look at many of the challenges faced in pushing the healthy built environment agenda forward. It provides a clear and theoretically sound framework to inform this work into the future. With an emphasis on context and the pursuit of equity,Jennifer L. Kent and Susan Thompson supply specific ways to better incorporate idiosyncrasies of place and culture into urban planninginterventionsfor health promotion. By chronicling the ways health and the built environment scholarship and practice can work together, Planning Australia's Healthy Built Environments enters into new theoretical and practicaldebates in this critically important area of research. This book will resonate with both health and built environment scholars and practitioners working to create sustainable and health-supportive urban environments
Description based on online resource; title from digital title page (viewed on April 22, 2019)
Keywords: City planning / Health aspects / Australia; Urban health / Australia